Sistem Informasi Manajemen Jalan Di Kota Ketapang - Juniardi, Ferry (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract Ketapang city as the district capital ketapan. Ketapang city is a growing city needs to be supported by systems that better traffic management. This study aimed to develop a management information system roads in the city of Ketapang. This study requires data traffic flow and road obtained from relevant agencies and field surveys. This study resulted in a system that is capable of handling data as well as the intersection of the road and display it in the form of a map. This system can help users in analyzing roads and signalized intersection or not. system can also help users filter the data that is based on certain criteria Keywords Traffic management, Roads, Intersections